Imbalance between subpopulations of regulatory T cells in COPD. Issue 12 (7th June 2013) - Hou, Jia; Sun, Yongchang; Hao, Yu; Zhuo, Jie; Liu, Xiaofang; Bai, Peng; Han, Junyan; Zheng, Xiwei; Zeng, Hui
Abstract : Background: Recent evidence indicates that human regulatory T cells (Tregs) are composed of three distinct subpopulations: CD25 ++ CD45RA + resting Tregs (rTregs), CD25 +++ CD45RA − activated Tregs (aTregs), which are suppressive, and CD25 ++ CD45RA − cytokine-secreting (Fr III) cells with pro-inflammatory capacity. Objectives: To evaluate the dynamic changes in circulating and pulmonary Treg subpopulations in smokers and patients with chronic obstructive pulmonary disease (COPD), and to explore their potential roles in COPD pathogenesis. Methods: Blood samples were obtained from 57 never-smokers, 32 smokers with normal lung function and 66 patients with COPD. Bronchoalveolar lavage (BAL) samples were taken from 12 never-smokers, 12 smokers and 18 patients with COPD. The proportions of Treg subpopulations and activated CD8 T cells were evaluated using flow cytometry. Results: In peripheral blood, increased proportions of rTregs, aTregs and Fr III cells were found in smokers compared with never-smokers, whereas patients with COPD showed decreased rTregs and aTregs, and significantly increased Fr III cells compared with smokers. The changes in Treg subpopulations, with an overall decrease in the (aTreg+rTreg):(Fr III) ratio, indicated that immune homeostasis favoured inflammation and correlated with enhanced CD8 T-cell activation (r=−0.399, p<0.001) and forced expiratory volume in 1 s (FEV1 ) % predicted value (r=0.435, p<0.001).The BAL (aTreg+rTreg):(Fr III) ratios displayed more robust correlations with FEV1 % predicted value (r=0.741, p<0.01) and activation of effector T cells (r=−0.763, p<0.001). Conclusions: The imbalance between the anti-inflammatory subsets (aTreg+rTreg) and the pro-inflammatory subset (Fr III) of Tregs may play an important role in COPD progression.